2020
DOI: 10.3390/ijerph17176371
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Reading Ability Gain in Kindergarten Children during COVID-19 School Closures

Abstract: By 15 April 2020, more than 1.5 billion students worldwide experienced school closures in an effort to slow the spread of a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), during the worldwide coronavirus disease 2019 (COVID-19) pandemic. These interruptions in formal in-person educational experiences caused adverse consequences on school-age children’s academic outcomes. Using a pre-existing database, we calculated changes in children’s reading ability without formal education… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 24 publications
3
66
0
1
Order By: Relevance
“…Although distance learning has vast possibilities to improve students' development, it still cannot replace the direct instruction model [24]. Bao et al [25] reported that "learning from home" reduces kindergarten students' reading ability. Wulandari and Purwanta [8] found a similar trend that the achievement of children's social-emotional skills decreased during the Covid-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although distance learning has vast possibilities to improve students' development, it still cannot replace the direct instruction model [24]. Bao et al [25] reported that "learning from home" reduces kindergarten students' reading ability. Wulandari and Purwanta [8] found a similar trend that the achievement of children's social-emotional skills decreased during the Covid-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some countries show the successful implementation of online learning [6]. Unfortunately, more researchers report the failures of online learning implementation [7]- [9]. Failures in carrying out online learning activities are also monitored in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study reveal data on the positive support of emergency remote teaching for 1st grade students who have reading problems. In the study conducted by Bao et al (2020), first reading activities are tried to be gained by emergency remote teaching. When the results of the study are compared with the previous scientific data obtained in face-to-face education, a decrease of 31% is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the published literature on the impact of the pandemic on education focuses on the stages of compulsory education, post-compulsory education, and, most especially, higher education. In only 60% of countries was distance education developed for the early childhood education stage [17], although 69% of students were unable to participate for various reasons [17], and in the case of the USA, nearly 40% of children did not participate regularly in virtualized education [35]. At this educational stage, and given the difficulty of virtualization of education due to the fact that contact, experimentation, and interaction between peers is fundamental [25,32,34], the family again becomes indispensable in order to develop the educational process [17,24,25,29,32,34], either by helping children to concentrate [25,29,33] or by accompanying them in activities [24,29,34], which again translates into an increase in educational inequalities [36].…”
Section: Introductionmentioning
confidence: 99%